Forest fires in Sumatra and air pollution in Malaysia: the law policies / Mohamed Shah Reza Noor Azman... [et al.] - Noor Azman, Mohamed Shah Reza; Mohd Ali, Nurul Ezaezrin; Azman Shah, Dayang Nor Emilia (2006)
This project studies the role and function of the Environmental Quality Act (EQA) 1974 and the ASEAN Treaties in dealing with the forest fires in Sumatra and the air pollution in Malaysia. Compensation and fines is not enough compared to the damage done. The aims of the research are to indicate the function and mechanism of the EQA and the ASEAN Treaty in dealing with the issue of the regional forest fires and and air pollution. The methods used in this research were through interviews and literature review among others. This research tries to find out what are the weaknesses in the enforcement of the law i.e. the EQA and the ASEAN Treaties regarding the issue of forest fires in Sumatra. We have looked at the previous and current situation in some of the cases and data significant to the research. Lack of financial resources to maintain and enhance the prevention of forest fire which caused several relevant bodies to ceased their duty. The polluter-pays principle is a good approach by the government but paying compensation had not stopped polluters. Thus, the research recommends various steps and solution in dealing with the issue of forest fires and the air pollution including reviewing the laws.